2012
DOI: 10.1093/schbul/sbr195
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Function in the Psychosis Spectrum: An [18F]-DOPA Imaging Study in Healthy Individuals With Auditory Hallucinations

Abstract: Background:The psychosis phenotype appears to exist in the population as a continuum, but it is not clear if subclinical psychotic symptoms and psychotic disorders share the same neurobiology. We investigated whether the dopaminergic dysfunction seen in psychotic disorders is also present in healthy, well-functioning people with hallucinations. Methods: We compared dopamine synthesis capacity (us-positron emission tomography imaging) in 16 healthy individuals with frequent persistent auditory verbal hallucinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 38 publications
4
83
0
Order By: Relevance
“…63,91 Dopamine levels have a prominent role in models of disorders like schizophrenia and PD, 95 including hallucinations. 96 Overall, there are many similarities in neurotransmitters between sleep-related perceptions and waking hallucinations, although the balance of neurotransmitter levels appears to be different. In REM sleep, sustained and high ACh levels from the forebrain and tegmental nucleus are important, whereas low ACh levels (or possibly transient ACh release) seem to characterize hallucinations.…”
Section: Differences In Brain Functions and Systemsmentioning
confidence: 99%
“…63,91 Dopamine levels have a prominent role in models of disorders like schizophrenia and PD, 95 including hallucinations. 96 Overall, there are many similarities in neurotransmitters between sleep-related perceptions and waking hallucinations, although the balance of neurotransmitter levels appears to be different. In REM sleep, sustained and high ACh levels from the forebrain and tegmental nucleus are important, whereas low ACh levels (or possibly transient ACh release) seem to characterize hallucinations.…”
Section: Differences In Brain Functions and Systemsmentioning
confidence: 99%
“…In a separate study, Disorganized traits, in non-clinical adults assessed with the SPQ, were positively correlated with D2 dopamine receptor availability, as measured by SPECT imaging with [123I]IBZM binding, in the right striatum [76]. Lastly, dopamine synthesis capacity in a non-clinical group with subclinical auditory hallucinatory phenomena did not differ from a control group; and schizotypal and other psychosis-spectrum symptoms were not related to dopamine synthesis capacity [77]. …”
Section: Neurobiological Studies: Structural and Neurochemical Findingsmentioning
confidence: 99%
“…However, little is known about the prevalence, clinical features and pathophysiology of psychosis in the broad SCA population or in particular SCAs. SCA 17 stands out as a hereditary ataxia which typically involves the basal ganglia, is often associated with psychosis, and is often considered a mimic of Huntington’s disease [21, 22, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the dopamine hypothesis of schizophrenia supposes that dysregulation of pre-synaptic dopamine in the striatum underlies the illness and susceptibility to psychosis [23, 24, 25, 26]. Schizophrenia has been associated with increased striatal dopamine synthesis as seen by PET radiotracer studies using 18 fluoro-dihydroxyphenyl-l-alanine (DOPA), an abnormality found to be specific to psychotic disorders compared to non-psychotic depression and other psychiatric disorders lacking psychosis [24, 35, 36]. Dopamine is synthesized from tyrosine through the action of tyrosine hydroxylase (TH), converting tyrosine to DOPA, which then is converted into dopamine [37].…”
Section: Introductionmentioning
confidence: 99%